2013
DOI: 10.3109/00207454.2012.761217
|View full text |Cite
|
Sign up to set email alerts
|

Association between the single-nucleotide polymorphism rs12425791 and ischemic stroke in Chinese populations: new data and meta-analysis

Abstract: The single-nucleotide polymorphism rs12425791 does not confer a substantial risk for ischemic stroke in Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In 2012, evidence from meta-analysis revealed that the rs12425791 was significantly associated with the risk of IS under a dominant genetic model [26, 27]. In contrast, an updated meta-analysis carried out in 2013 showed that no significant association between the rs12425791 and IS risk [28]. Similar to the negative data, we found in this study that the rs12425791 did not confer a substantial risk for IS in the Chinese Han population.…”
Section: Discussionsupporting
confidence: 70%
“…In 2012, evidence from meta-analysis revealed that the rs12425791 was significantly associated with the risk of IS under a dominant genetic model [26, 27]. In contrast, an updated meta-analysis carried out in 2013 showed that no significant association between the rs12425791 and IS risk [28]. Similar to the negative data, we found in this study that the rs12425791 did not confer a substantial risk for IS in the Chinese Han population.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies showed that rs12425791 is relative to ischemic stroke risk in Asian population (Lian et al, 2012;Zhang et al, 2016). However, the contradictory studies about association between rs12425791 or NINJ2 gene and ischemic stroke also emerge in Chinese Han population (Chen et al, 2010;Ding et al, 2011;Tong et al, 2011;Wan Gu et al, 2013;Xie et al, 2013). In our study, we found variants rs12425791 of the NINJ2 gene to be strongest associated with ischemic stroke in Chinese Mongolian ethnicity, and A alleles increase the risk of ischemic stroke, indicating the rs12425791 of the NINJ2 gene might play function in the insult of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%